Simulación de silanización de partículas de grafeno oxidadas mediante el uso de APTES en reactor PBR a escala y tamaño real (2020)
The functionalization of oxidized graphene is a method that has been increasingly studied in recent years for biological, medical and biomedical purposes. The use of aminosilanes such as APTES is of great interest to silanize the surface of oxidized graphene nanoparticles, so a simulation of the surface reaction was performed: first at various scale sizes for a 23-particle porous membrane reactor and then modeled at real size for a packed bed reactor, at different initial conditions, using COMSOL Multyphysics 5.3 software. By simulating the scale reactor, a diffusivity value of 3, 487 * 10/6m2/8 could be obtained, which would be used as a base parameter to simulate the packed bed reactor at real size. Experimentation resulted that the radius size in the scaled reactor influences both diffusivity and concentration, while the full-size PBR required an initial APTES concentration of 3 mol m3 and equilibrium constant of 0.1 to obtain...